Volume 4: Heat Transfer, Parts a and B 2012
DOI: 10.1115/gt2012-69329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Friction on the Blow-Down Behavior of an Aramid Fiber Brush Seal

Abstract: Aramid fiber brush seals are ultra-low leakage, compliant sealing elements for turbomachinery applications. Such seals are applicable in the Aviation, Energy, and Oil and Gas markets as either air-air seals or air-oil seals. In the present study, the influence of friction present between the front plate and upstream side of the bristle pack of an aramid fiber brush seal is experimentally investigated. With the bristle pack fully exposed on the upstream side of the seal, the bristles are shown to blow down and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Franceschini et al 20 developed a large radial movement brush seal to accommodate a much larger range of rotor excursion avoided excessive bristles wear. Ruggiero 21 reported that the grooves in upstream cover plate could enhance the bristle blow-down in an aramid fiber brush seal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Franceschini et al 20 developed a large radial movement brush seal to accommodate a much larger range of rotor excursion avoided excessive bristles wear. Ruggiero 21 reported that the grooves in upstream cover plate could enhance the bristle blow-down in an aramid fiber brush seal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To overcome the abrasive nature and undesired structural effect of bristles, novel materials have been studied. 12,13 However, Haynes 25 is still preferred for steam turbine brush seals where high temperature tolerance and resilient bristles are needed. 14 Heat generation effects arising from friction were investigated numerically 15 and experimentally, suggesting a theoretical heat generation model.…”
Section: Introductionmentioning
confidence: 99%